2007
DOI: 10.1007/s10557-007-6056-9
|View full text |Cite
|
Sign up to set email alerts
|

l-carnitine as an Adjunct Therapy to Percutaneous Coronary Intervention for Non-ST Elevation Myocardial Infarction

Abstract: L: -carnitine adjunct therapy appears to be associated with a reduced level of cardiac markers in patients with NSTEMI. These results support a larger clinical trial to investigate the effect of L: -carnitine on cardiac events following PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
0
16
0
5
Order By: Relevance
“…L-carnitine reduces early mortality but not overall risk of death or heart failure at 6 months [127]. L-carnitine supplementation also prevents ventricular enlargement and dysfunction, reduces the infarct size and cardiac biomarkers, and diminishes the total number of cardiac events including cardiac deaths and nonfatal infarction [128,129]. Xue and colleagues suggest that the beneficial effects of L-carnitine in cardiovascular disease are due to the resumption of normal oxidative metabolism and restoration of myocardial energy reserves [128,129].…”
Section: Introductionmentioning
confidence: 99%
“…L-carnitine reduces early mortality but not overall risk of death or heart failure at 6 months [127]. L-carnitine supplementation also prevents ventricular enlargement and dysfunction, reduces the infarct size and cardiac biomarkers, and diminishes the total number of cardiac events including cardiac deaths and nonfatal infarction [128,129]. Xue and colleagues suggest that the beneficial effects of L-carnitine in cardiovascular disease are due to the resumption of normal oxidative metabolism and restoration of myocardial energy reserves [128,129].…”
Section: Introductionmentioning
confidence: 99%
“…16 In patients with non-ST elevation MI, L-carnitine reduced the release of both creatine-MB and troponin-I. 17 However, the effect of L-carnitine on overall clinical outcome has not been determined. Other anti-oxidants such as α-lipoic acid (the level of which significantly declines with age) 18 and melatonin (an anti-oxidant and a neurohormone produced by the pineal gland) 19 are currently being tested in clinical trials for cardiovascular-related indications.…”
Section: Introductionmentioning
confidence: 99%
“…In chronic heart disease patients, L-carnitine administration over 12 months has been shown to attenuate left ventricular dilatation and prevent ventricular remodeling while reducing incidence of chronic heart failure and death. The protective effects of L-carnitine supplementation also extend to acute myocardial infarction (MI); following acute MI, prompt L-carnitine administration and subsequent oral maintenance therapy has been shown to attenuate progressive left ventricular dilatation and appears to reduce myocardial injury through improving carbohydrate metabolism and reducing the toxicity of high free fatty acid levels [5,6]. A recent systematic review and meta-analysis of 13 controlled trials by DiNicolantonio et al found that L-carnitine supplementation was associated with a significant reduction in all-cause mortality, ventricular arrhythmia, and angina in the setting of acute MI [7].…”
Section: Introductionmentioning
confidence: 99%